2022
DOI: 10.1038/s41598-022-15193-8
|View full text |Cite
|
Sign up to set email alerts
|

Bioflocculant produced by Bacillus velezensis and its potential application in brewery wastewater treatment

Abstract: This study was designed to evaluate the potential of bioflocculant producing strains isolated from wastewater sludge. According to the Plackett–Burman design, the response surface revealed glucose, magnesium sulfate, and ammonium sulfate as critical media components of the nutritional source, whereas the central composite design affirmed an optimum concentration of the critical nutritional source as 16.0 g/l (glucose), 3.5 g/l magnesium sulfate heptahydrate (MgSO4.7H2O), and 1.6 g/l ammonium sulfate ( (NH4)2SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
3
9
0
Order By: Relevance
“…Therefore, the removal the efficiency of the bioflocculant implies its potential industrial applicability. The results were in agreement with those obtained by Agunbiade et al [60] and Pathak et al [61], whereby the bioflocculants were efficient in removing pollutants in wastewater.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the removal the efficiency of the bioflocculant implies its potential industrial applicability. The results were in agreement with those obtained by Agunbiade et al [60] and Pathak et al [61], whereby the bioflocculants were efficient in removing pollutants in wastewater.…”
Section: Discussionsupporting
confidence: 92%
“…Only 5.25 (PM-1) and 6.00 (BC06) mg/L were found in this study, which was less than the standard BOD of aquaculture effluent (≤20 mg/L). The result of Bacilli species was similar to the result of B. velezensis, which showed 46% of BOD removal [32]. While isolated cellulolytic Bacillus had reduced BOD by 90% [33], another B. subtilis was 93% of BOD removal [37].…”
Section: Biochemical Oxygen Demand (Bod5)supporting
confidence: 54%
“…It might be because they have co-metabolism to degrade or trap the particle suspension in the water sample. The result was according to the study of B. velezensis that showed TSS removal of brewery wastewater for 55% [32]. In an aquaculture pond, the solid suspension will be overshadowed by light through water which affects the primary production process of water.…”
Section: Total Suspended Solid (Tss)mentioning
confidence: 97%
See 1 more Smart Citation
“…The analysis of variance (ANOVA) for the quadratic model was summarized in Table 2. Similarly to the study of Agunbiade et al (2022), the model F-value of 99.09 indicated that the model was highly statistically significant at p < 0.0001. The lack of fit F-value and p-value was found to be 4.4 and 0.093, indicating that the suitability of the model to predict the variations.…”
Section: Results Optimization Of Fermentation Medium Compositionmentioning
confidence: 71%